Economics of converged, internet-based networks 7th international workshop on internet charging and QoS technologies, ICQT 2011, Paris, France, October 24, 2011. proceedings - Cohen, Johanne; Maillé, Patrick; Stiller, Burkhard 1965- (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 6th International Workshop on Internet Charging and QoS Technologies, ICQT 2011, held in Paris, France, in October 2011 collocated with the 7th International Conference on Network and Service Management. The 6 revised full papers presented together with an abstract of a keynote paper were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on service guarantees, evaluation of pricing schemes, and inter-domain services.